Immunogenicity of a Virus-Like-Particle Vaccine Containing Multiple Antigenic Epitopes of Toxoplasma gondii Against Acute and Chronic Toxoplasmosis in Mice - Guo, Jingjing; Zhou, Aihua; Sun, Xiahui; Sha, Wenchao; Ai, Kang; Pan, Ge; Zhou, Chunxue; Zhou, Huaiyu; Cong, Hua; He, Shenyi (Frontiers in Immunology, 2019)
There is no effective protective vaccine against human toxoplasmosis, which is a potential threat to nearly a third of the world population. Vaccines based on virus-like particles (VLPs) have been highly successful in humans for many years, but have rarely been applied against Toxoplasma gondii infection. In this study, we inserted a B cell epitope (SAG182−102 or SAG1301−320), a CD8+ cell epitope (HF10 or ROP7), and a CD4+ cell epitope (AS15) of T. gondii into a truncated HBcΔ(amino acids1–149) particle to construct four chimeric VLP vaccine formulations, i.e., HBcΔH82, HBcΔH301, HBcΔ R82, and HBcΔ R301. When these chimeric HBc particles were expressed in Escherichia coli, they showed icosahedral morphology similar to that of the original VLPs and were evaluated as vaccine formulations against acute and chronic toxoplasmosis in a mouse model (BALB/c mice (H-2d). All these chimeric HBc VLPs induced strong humoral and cellular immune responses with high IgG antibody titers and interferon(IFN)-γ production. Only the mice immunized with HBcΔH82 showed prolonged survival time (15.6 ± 3.8 vs. 5.6 ± 0.8 days) against acute infection with RH tachyzoites and decrease in brain parasite load (1,454 ± 239 vs. 2,091 ± 263) against chronic infection with Prugniuad cysts, as compared to the findings for the control group. These findings suggest that HBc VLPs would act as an effective carrier for delivering effective multiple antigenic epitopes and would be beneficial for developing a safe and long-acting vaccine against toxoplasmosis.